The mycota : a comprehensive treatise on fungi as experimental systems for basic and applied research / IX, Fungal Associations - Esser, Karl , 1924- (Springer, 2012)
This book examines fungal associations as found in mycorrhizas, lichens and other fungal symbioses. The revised, updated second edition incorporates recent findings on molecular interaction between fungi and plants or bacteria, as a prerequisite for symbioses